Comparison of Photo ElectroFenton Process(PEF) and combination of PEF Process and Membrane Bioreactor in the treatment of Landfill Leachate. (2016) - Nivya, T.K.; Minimol Pieus, T.
Abstract: Landfill leachate treatment is an integral part of municipal solid waste management. The conventional biological treatment of landfill leachate is limited because of the presence of toxic contaminants and recalcitrant organics. Among Advanced Oxidation processes(AOPs), Photo Electro Fenton Process(PEF) can be used effectively for the treatment of highly contaminated water. In the treatment of leachate by biological methods, Membrane Bioreactor(MBR) is efficient while considering the effluent quality. So a combination of PEF followed by MBR treatment is adopted in this study. The percentage removal of pollutants -TSS, BOD, COD, Ammonia Nitrogen, Phosphate, Sulphate, Sulphide and Chloride from landfill leachate after PEF process is 89.3, 71.9, 83.6, 100, 58, 92.3, 65 and 65 respectively. The percentage removal of the same pollutant parameters after combined treatment of PEF followed by MBR is 95.5, 90.2, 96.2, 100, 82.7, 93.3, 88.2 and 88.3. The pollutant removal efficiency is increased by adopting combined treatment –PEF followed by MBR.